Lipoprotein (a) and Lipoprotein-associated Phospholipase A2 as Atherosclerosis Risk Factors (oxLDL) in Men with Central Obesity - Nelly Sari; Andi Wijaya; Ilhamjaya Patellongi (The Prodia Education and Research Institute (PERI), 2011)
BACKGROUND: The increasing prevalence of obesity in Indonesia triggers a lot of research interest to overcome it. Obesity has a very important role as atherosclerosis and cardiovascular risk factors. The presence of oxidized LDL (oxLDL) on the vascular wall is a marker of atherosclerosis. The increase of Lipoprotein(a) (Lp(a)) and Lipoprotein associate phospholipase A2 (LpPLA2) occurs in patients with coronary artery disease (CAD), myocardial infarction, and unstable angina. It is well accepted that obesity is closely related to atherosclerosis and cardiovascular risk factors. However, correlation between Lp(a), LpPLA2 and oxLDL in central obesity has not yet been investigated. The aim of this study was to observing the correlation between Lp(a), LpPLA2 and oxLDL in early central obesity.METHODS: An observational study with cross-sectional design on 76 men with central obesity, aged 30-67 years, was conducted. Central obesity was characterized by waist circumference >90 cm. Test of Lp(a) was performed by turbidimetric method and that of LpPLA2 was performed by sandwich enzyme immunoassay. Test of oxLDL was performed by ELISA. All statistical analyses were carried out using SPSS for Windows v.11.5 at a significance level of p<0.05. The Pearson and Spearman’s Rho correlation coefficient was used to assess the correlation between Lp(a), LpPLA2 and oxLDL. Obese men with acute inflammation (hsCRP > 10 mg/L), renal failure (Creatinine >1.5 mg/dL) and consumed antiinflammation were excluded from this study.RESULTS: The concentration of LpPLA2 had a linear correlation (r=-0.340, p=0.003) with the increase of oxLDL concentration. However, concentration of Lp(a) did not have linear correlation (r = 0.025) with increase of oxLDL concentration. This finding indicates that concentration of LpPLA2 had a negative correlation with increase of concentration of oxLDL. In addition, Lp(a) appears not to correlate with oxLDL significantly.CONCLUSION: The study showed there was a significant correlation between concentration of LpPLA2 and concentration of oxLDL in men with central obesity. Higher concentration of LpPLA2 correlated with lower concentration of oxLDL.KEYWORDS: Lp(a), LpPLA2, oxLDL, atherosclerosis, central obesity